Resuming ophthalmology practice armoured with a bulletproof plan due to COVID 19 - Sandhya Ramachandra; Varsha V (Journal of Clinical and Biomedical Sciences)
Covid 19, a deadly pandemic which started in China’s Wuhan province in December has impacted the lives of millions of people physically, mentally and economically. In view of the pandemic, the Government of India instituted a nation-wide lockdown on 24th march 2020.All non-emergency outpatient departments and elective surgeries were deferred. Ophthalmology, predominantly an elective, non-emergency branch was severely affected.1 However, we have to learn to live with this virus, which means adapting to the “new normal” and resuming elective ophthalmology practice